Antimicrobial Activity of Methanolic Extracts of Myrtus Communis L. and Eucalyptus Galbie and their Combination with Calcium Hydroxide Powder against Enterococcus Faecalis - Maryam Raoof; Moj Khaleghi; Najmeh Siasar; Sakineh Mohannadalizadeh; Jahangir Haghani; Sara Amanpour (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: The goal of endodontic therapy is the reduction or elimination of microorganisms from the root canal system. The use of intracanal medicament between treatment appointments is recommended in order to eliminate any remainang microorganisms in the pulp space. Purpose: The aim of the present study was to investigate the antimicrobial activity of methanolic extracts of Myrtus communisL. and Eucalyptus galbie, their combination with calcium hydroxide powder; combination of calcium hydroxide powder with water, and ready-to-use calcium hydroxide paste with iodoform; against Enterococcus faecalis. Materials and Method: In this experimental study, after gathering the plants, their methanolic extracts were obtained by masceration method. The diameters of inhibition zone of all mentioned materials were determined by agar diffusion test. Minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC); and anti biofilm effect of the materials that showed antibacterial effect in agar diffusion test, were then evaluated by tube dilution test, and microtiter plate assay followed by colorimetric crystal violet methods, respectively. Results: After 48 hours, both herbal extracts showed antimicrobial effect. However, combination of calcium hydroxide with extracts produced no zone of inhibition. The mean inhibition zone of Eucalyptus extract was more than that of Myrtus. However, the results of ANOVA test, showed that there was no significant difference between the antibacterial effect of Eucalyptus galbie, Myrtus communisL. and positive control (Cefoxitin) (p Value= 0.987). The MIC for both extracts were 12.5 mg/ml. MBC evaluation of the two methanolic extracts showed no bactericidal effect on Enterococcus faecalis. Based on ELISA analysis, biofilm formation in response to different sub-MIC concentrations of both extracts was scored as weak to moderate. Conclusion: The methanolic extracts of Eucalyptus galbie and Myrtus communis L. in combination with calcium hydroxide powder were not able to eliminate Enterococcus faecalis within 48 hours.